Some observations on the penetration of antibiotics through mucus in vitro. Issue 4 (July 1966) - Saggers, B. A.; Lawson, David
Abstract : A study has been made on the penetration values in vitro of antibiotics through hog gastric mucin at p H 7·4. Determinations have also been done on the binding of antibiotics to mucus and human plasma. The mucolytic agent N-acetyl cysteine has been studied in regard to its effect on antibiotics penetrating mucus and for any possible inactivation of antibiotics.